Association of CTLA-4 polymorphisms with hematologic malignancy susceptibility: a meta-analysis - Yan, Xuefen; Zhang, Nana; Wang, Gang (Frontiers in Oncology, 2024)
BackgroundRecent studies have reported an association between Cytotoxic T-lymphocyte antigen-4 (CTLA-4) polymorphisms and hematologic malignancy susceptibility, while the results remain inconsistent. Hence, we performed a meta-analysis to investigate the association between CTLA-4 polymorphisms with hematologic malignancy susceptibility.MethodsA comprehensive and systematic search of Cochrane Library, PubMed, Embase databases was performed up to Sep. 20, 2024. The pooled odds ratio (OR) and its 95% confidence interval (CI) were used to determine the strength of the association between CTLA-4 polymorphisms and hematologic malignancy susceptibility. Statistical analysis was performed in STATA 12.0.ResultsA total of 13 studies concerning the CTLA-4 49A/G, CTLA-4 60A/G, CTLA-4 318T/C, CTLA-4 1661A/G, and CTLA-4 319C/T polymorphisms were included in the meta-analysis. The pooled results suggested the CTLA-4 49A/G polymorphism was significantly associated with an increased hematologic malignancy risk (AA vs. GA+GG: OR = 1.77, 95% CI = 1.56-2.02), especially in NHL, multiple myeloma, and leukemia. Similarly, CTLA-4 319C/T polymorphism was found to be associated with decreased chronic lymphocytic leukemia risk. There was no significant association between the CTLA-4 60A/G, 318T/C, and 1661A/G polymorphism and hematologic malignancy risk.ConclusionCTLA-4 49A/G and 319C/T polymorphisms were associated with hematologic malignancy susceptibility.